Protein-protein interactions in a geminivirus-cassava system - Ncube Kanyika, Busisiwe (My University, 2022)
Cassava as a hardy drought tolerant crop that offers economic value in poor rural communities as a low input cost crop to farm for rural development. It provides nutritional needs as a gluten-free carbohydrate source is an essential raw material in industrial applications to produce renewable energy, starch, paper, glue, and is relevant to pharmaceuticals and mining. However, cassava is subject to disease, especially those caused by geminiviruses. Geminiviruses can devastate yields of cassava and thus negatively impact the cassava value chain. South African cassava mosaic virus (SACMV) (family Geminiviridae) is an economically significant plant virus that hijacks the cassava (host) genome replication machinery for its own multiplication and inevitable plant deterioration of plant health. SACMV systemic movement results in global subcellular changes that alter host gene expression and inhibit plant defence mechanisms. The ability of SACMV to replicate and proliferate is determined by the host availability of a matrix of proteins and metabolites that upon direct/indirect interaction promote virus movement and evasion of plant defences. Transcriptomic studies and virus-host interaction assays have generated a plethora of biologically significant data on tolerant and susceptible host-virus responses within cassava and other species. However, a complete understanding of viral protein mechanisms and clear solutions towards resistance and increased yield remain elusive. Therefore, the objectives of the research reported here were to identify resistance associated genes from transcriptomic data obtained from plants infected with geminiviruses and to gain an understanding of geminiviral systemic movement via SACMV movement protein interactions. Yeast two-hybrid (Y2H) assays were utilized in the identification of cassava host proteins interacting with the MP cell-cell movement protein of SACMV. Monoclonal antibodies were raised up in rabbit against MP antigenic fragments to co-immunoprecipitate MP-infected host protein (MP-IHP) complexes. In planta CRISPR-mediated gene editing in cassava protoplasts was carried out to ascertain the role of three identified host interactors from Y2H assays, namely, nuclear pore complex protein (NUP98), histone-lysine N methyltransferase ATX4-like (SDG16) and casein kinase 1-like protein HD16 (CKL1) in SACMV accumulation. From a total of 150 million analysed Y2H interactions, 12 novel interactors were identified and ranked according to their predicted biological scores (PBS) from very high to moderate. These were: CKL1 and NUP98A (Very high), lysine--tRNA ligase, cytoplasmic-like (KRS1) (High), photosystem I reaction centre subunit II, chloroplastic-like (PsaD), probable galactinol-sucrose galactosyltransferase 2 (SIP2) (Good) and SDG16, purine uptake permease 1-like (PUP1), homoserine kinase (HSK), phosphatidylinositol 3,4,5-trisphosphate 3-phosphatase and protein-tyrosine-phosphatase (PTEN2A), acyl-CoA N-acyltransferase (NAT), ethylene-responsive transcription factor iv ABR1-like (ABR1-like) and protein LIGHT-DEPENDENT SHORT HYPOCOTYLS 4-like (LSH) proteins (Moderate). Co-immunoprecipitation identified seven highly significant proteins, namely gylycine decarboxylase P-protein (GLDP2), heat shock protein 90 (HSP90), histone superfamily protein (H4), ATP citrate lyase subunit B (ACLB-2), sucrose synthase activity (SUS4), ATPase, AAA-type protein (CDC48C) and mitochondrial malate dehydrogenase (mMDH1). Gene editing of NUP98, SDG16 and CKL1 resulted in a down regulation of SACMV accumulation. The protein network of interacting proteins showed that BC1 encoded movement protein (MP) relies on the host for post-translational modifications for its functionality. It also plays a multifunctional role by manipulating host proteins to potentially mediate viral genome movement and activation, and further interferes with global host metabolism contributing to disease symptoms
A thesis submitted in fulfilment of the academic requirements for the degree of Doctor of Philosophy in Molecular and Cell Biology to the Faculty of Science, University of the Witwatersrand, Johannesburg, 2022